3,5-Dimethyladamantan-1-amine Restores Short-term Synaptic Plasticity by Changing Function of Excitatory Amino Acid Transporters in Mouse Model of Spinocerebellar Ataxia Type 1 - Olga S. Belozor; Alex A. Vasilev; Alexandra G. Mileiko; Liudmila D. Mosina; Ilya G. Mikhailov; Andrey N. Shuvaev; Anton N. Shuvaev (Анналы клинической и экспериментальной неврологии, 2024)
Introduction. Memantine is an agent that used for treatment of Alzheimer's type dementia. Memantine considerably reduces the effects of neurodegeneration, may potentially slow down the neurodegenerative changes in the cerebellum and may act as treatment of choice for spinocerebellar ataxia type 1 (SCA 1).